Strategic B2B marketing planning with an international focus for the software development provider ‘East At-lantic Engineering’, using Germany as exemplary case - Weger, Mathias (2013)
The following project-based master thesis introduces the Lisbon based software devel-opment provider EAST ATLANTIC ENGINEERING to international strategic B2B marketing planning. So far the company has exclusively gained assignments through relationships and word-of-mouth recommendations. It has never actively done marketing. Therefore the work starts by a practical oriented literature review about B2B marketing including its distinction from B2C marketing. Afterwards the four steps of the strategic marketing planning process get described in theory, building the basis for the development of EAE’s tailor-made marketing strategy. The concentration lays on the situation analysis and the strategy development with its program. Accommodating the company’s demand to use Germany as exemplary case, the international focus lies on this EU country. The situation analysis includes an internal as well as an external analysis revealing EAE a promising perspective for success on the German market. With the defined target mar-ket the strategy development starts by contrasting internal strengths and weaknesses with external opportunities and threats. Considering these approaches, PORTER’s three generic strategies get discussed and the appropriate one gets chosen. The four Ps repre-sent the tools to realize the strategy. Again accommodating EAE’s demand, the promo-tional tool plays the decisive role in this case. Finally the work ends with a conclusion, summarizing the most important aspects and findings.